1992
DOI: 10.1172/jci115827
|View full text |Cite
|
Sign up to set email alerts
|

Activin and inhibin in the human adrenal gland. Regulation and differential effects in fetal and adult cells.

Abstract: Recent experimental data have revealed that activins and inhibins exert pivotal effects on development. As part of our studies on growth and differentiation of the human fetal adrenal gland, we examined the subunit localization, as well as the mitogenic and steroidogenic actions of activin and inhibin in human fetal and adult adrenals. All three activin and inhibin subunit proteins (a, ,A, and #B) were detected in the fetal and adult adre-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
91
0
1

Year Published

1996
1996
2001
2001

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 39 publications
13
91
0
1
Order By: Relevance
“…Although in early studies zona glomerulosa was suggested to be immunohistochemically positive for inhibin (Spencer et al 1992), most recent studies have suggested an inner zonespecific staining pattern (McCluggage et al 1998). We also showed negative inhibin immunostaining in the zona glomerulosa, weak staining in the zona fasciculata, and very strong staining in the zona reticularis.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Although in early studies zona glomerulosa was suggested to be immunohistochemically positive for inhibin (Spencer et al 1992), most recent studies have suggested an inner zonespecific staining pattern (McCluggage et al 1998). We also showed negative inhibin immunostaining in the zona glomerulosa, weak staining in the zona fasciculata, and very strong staining in the zona reticularis.…”
Section: Discussionsupporting
confidence: 52%
“…Both inhibin and subunit mRNA species and peptides can be detected in adrenal cortex, but not in the medulla (Meunier et al 1988, Voutilainen et al 1991, Spencer et al 1992, McCluggage et al 1998. The first reports suggested all adrenocortical tumours to be inhibin positive (Chivite et al 1998, McCluggage et al 1998.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibin mRNA has been demonstrated in the ovine (Crawford et al 1987) and human (Voutilainen et al 1991) adrenal cortex and its expression has been shown to be upregulated by adrenocorticotrophic hormone (ACTH). Immunopositivity for inhibin has been reported in the rat (Merchenthaler et al 1991) and human (Spencer et al 1992) adrenal cortex. There is less information on the expression of subunits.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma immunoreactive inhibin levels are higher in the adrenal veins than in vena cava or the peripheral circulation (Nishi et al 1995) and normal adrenocortical cells in culture secrete inhibin-like immunoreactive material (Haji et al 1991, Spencer et al 1992. While this may reflect production of mature inhibin dimer it may also indicate the presence of free subunit which may crossreact in the assay.…”
Section: Introductionmentioning
confidence: 99%